Mystical mushrooms : discover the magic & folklore of fantastic fungi - Kane, Aurora (Rock Point, an imprint of The Quarto Group, 2023)
"In Mystical Mushrooms, explore the magical properties, mythological connections, and symbolic qualities of ever-intriguing fungi"--